The trial of Dominic Cummings: rules and reason in the pandemic - Clarke, M (Wiley, 2021)
The trip by Dominic Cummings, British Prime Minister Boris Johnson's then right‐hand man, to Durham in April 2020, in seeming violation of the rules of social distancing he had helped put in place, led to intense media scrutiny and public outrage. That there might be ‘One rule for them, and one for the rest of us’ became a stick to beat the government with and arguably contributed to Cummings’ eventual departure from Downing Street. This article focuses on the defence he put forward at the time. Rather than breaking the rules, he had followed them, he argued, providing a series of justifications, one of which led to widespread ridicule, the rest being largely dismissed. Rules of social distancing and the public's compliance with them have been of global concern during the coronavirus pandemic. I argue that the Cummings incident shows both the complexity of ordinary notions of what it means to follow a rule, and a tendency for that complexity to be left undiscussed in both scientific and public debate – to all our detriment.